Health of Incarcerated Women: A Gender-Specific Study of India - Sanghamitra Baladhikari, Somabha Bandopadhay, Dr. Shambhu Prasad Chakrabarty (International Journal of Advanced Science and Technology, 2020)
The perception of women’s health in one of the most neglected aspect in correctional homes. Apart from overall deprivation, women have been subjected to multiple victimisation either in the hand of non-state or state entities, as in the case of correctional homes. It is important for the administration to understand the specific health standards which are bare minimum for women inmates and act accordingly. The recent pandemic further exposed the challenges inherent in the correctional homes. The century old legislation on correctional homes in India must give way to the new laws which should include the major health issues of women. Laws and rights must not only be inside the law books but should be in practice to protect the rights of the people of the country. This research put the facts together and analyses the vulnerability of women inmates and includes the reproductive health challenges to make this work a medico legal piece.